PENGARUH MEDIA RANTAI GAMBAR TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA RENGAT BARAT KABUPATEN INDRAGIRI HULU - Mutiara Ayu Familiza; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :This study aims to determine the effect of media images chain on the ability to know the concept of numbers in children aged 4-5 years in TK Negeri Pembina Rengat Barat District Indragiri Hulu. The population in this study that children B2 classes totaling 20 children and sample in this study amounted to 20 children. The method used pre-experimental design with one group pretest posttest design that experiments conducted on one group alone with no comparison group. This type of instrument used in this study is to use the observation and documentation to take notes about events that occurred during the treatment given. Based on the results obtained by testing the hypothesis that there are significant media image chain on the ability to know the concept of numbers in children aged 4-5 years in TK Negeri Pembina Rengat Barat District Indragiri Hulu. Thus known t count (18.523) or significance (0.000), because sig < 0.05, it can be concluded that there are differences in the ability to know the concept of numbers on students significant before and after using media images chain in the learning. Hypothesis testing can be seen on t = 18.523 > table = 1,729. It has been suggested that there are significant differences in the results between the pretest and posttest. Media influence on ability to know your chain drawing numbers concept in children aged 4-5 years in TK Negeri Pembina Rengat Barat District Indragiri Hulu amounted to 72.48%.Key Words: Recognize the Concept of Number, medium chain pictures